Clinical manifestations and treatment of Cherubism: An integrative literature review (Research, Society and Development, 2025)
Cherubism is a rare bone disease that mainly affects children in early childhood, being characterized by abnormal and progressive growth of the mandible and maxilla. The pathology was first described in 1933 by Jones and consists of the exaggerated development of these bone structures, caused by the formation of atypical tissues, which results in the appearance of facial lesions that may compromise both aesthetics and masticatory function. The present study aims to present the main clinical findings and to discuss the most frequently described clinical manifestations and therapeutic approaches in the scientific literature, in order to assist in the diagnosis and treatment of cherubic lesions. For the construction of the bibliographic research, consolidated scientific databases were used, including SciELO, MEDLINE, and LILACS, allowing the selection of relevant articles on the subject. Regarding treatment, it is observed that there is still no single and standardized protocol. Therefore, the choice of therapeutic approach should always be based on the specific characteristics of each clinical case, considering individual factors and patient particularities, in order to provide more adequate and effective management.